2023
DOI: 10.3390/su15053908
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Interdependencies between Education and the Labor Market in the View of Sustainable Development and Investment in the Educational System

Abstract: Education represents the basic pillar of preparing individuals for integration into the labor market, but also is a crucial component of ensuring sustainable development. The purpose of this research was to identify the type of influences existing between education and the labor market in EU member countries in the context of different levels of investment in the educational system. Cluster analysis and the ordinary least squared method were used to identify the type of influences between the indicators charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
1
2
0
1
Order By: Relevance
“…03, March 2023: pp. 100-108 Strategic investments in education and training programs tailored to the needs of the local job market can contribute to a skilled and work-ready workforce [24]. The negative association between education levels and unemployment rates is in line with existing literature, which emphasizes the importance of educational attainment in reducing unemployment [42].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…03, March 2023: pp. 100-108 Strategic investments in education and training programs tailored to the needs of the local job market can contribute to a skilled and work-ready workforce [24]. The negative association between education levels and unemployment rates is in line with existing literature, which emphasizes the importance of educational attainment in reducing unemployment [42].…”
Section: Discussionsupporting
confidence: 61%
“…Higher educational attainment is generally associated with lower unemployment rates, known as the "education premium" [23]. However, studies have shown that a mismatch between educational qualifications and job requirements can lead to underemployment and contribute to higher unemployment rates [24]. Understanding this dynamic is crucial for addressing unemployment in West Java Province and developing targeted interventions.…”
Section: Education and Unemploymentmentioning
confidence: 99%
“…Development effect. The education level of people affects the level of savings, investment rates and investment areas, employment status, income distribution, and many macro variables in the economy [40][41][42][43][44]. At the same time, the successes achieved in educational life increase the productivity of individuals by raising their living standards, increase the opportunities for growth and innovation, prevent social corruption and crime, and decrease public health expenditures and social assistance needs [45][46][47][48].…”
Section: Socioeconomic Impact Of Educationmentioning
confidence: 99%
“…Дослідження науковців з різних країн підтверджують, що державні інвестиції в освіту та навчання мають багато переваг і позитивних впливів на економіку та суспільство через підвищення кваліфікації та інтелектуального рівня працівників, тим самим зменшуючи безробіття та бідність у країні (Tudor et al, 2023;Ukaj et al, 2023). Освіта підвищує продуктивність і креативність людей, а також сприяє розвитку підприємництва та передових технологій, розвиваючи капітал, заснований на знаннях (Dia Kamgnia and Bergaly, 2022;Seidl, 2022).…”
unclassified